Active power control of a flywheel energy storage system for wind energy applications - Suvire, Gaston Orlando (2012)
The integration of wind power generation in power systems is steadily increasing around the world. This incorporation can bring problems onto the dynamics of power systems owing to the lack of controllability over the wind and the type of generation used. In this work, a distribution static synchronous compensator (DSTATCOM) coupled with a flywheel energy storage system (FESS) is used to mitigate problems introduced by wind generation in the electric system. A dynamic model of the DSTATCOM/FESS device is briefly presented and a technique to control the active power exchanged between the device and the power system is proposed. The control technique is based on fuzzy logic and a special filter. Tests of the behaviour of the device are analysed when combined with wind generation in the electric system. Results show an overall satisfactory performance of the proposed control technique along with the high effectiveness of the device used to smooth the active power fluctuations of a wind generator.